Anxiety and Stress among Engineering Students toward Accounting Subjects - Larracilla-Salazar, Némesis; Camacho-Morales, María de los Ángeles; Peralta-Vázquez, Norma Edith (TEM Journal, 2025)
The attitudes of college students towards accounting subjects are of interest, in particular, emotions that generate anxiety and stress can trigger poor academic performance. The aim of this article is to analyze the level of anxiety and stress generated by accounting subjects for Engineering students at the Technological Institute of Veracruz and to propose a new scale: anxiety and stress scale towards accounting which was applied on 214 students. The results of the Bartlett KMO sphericity test (.923), the calculated X2, 1527.930 with 45 df > X2t, Sig. 0.000 p < 0.01, MSA (.852 to .949) and with a determinant value of 0.001, indicate high correlations in the variables. The internal consistency obtained α=0.733 (pooled), 0.923 individual. The results determine the existence of the two components.